2013
DOI: 10.3174/ajnr.a3718
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis on the Diagnostic Performance of 18F-FDG and 11C-Methionine PET for Differentiating Brain Tumors

Abstract: SUMMARY:18 F-FDG-PET has been widely used in patients with brain tumors. However, the reported sensitivity and specificity of 18 F-FDG-PET for brain tumor differentiation varied greatly. We performed this meta-analysis to systematically assess the diagnostic performance of 18 F-FDG-PET in differentiating brain tumors. The diagnostic performance of 11 C-methionine PET was assessed for compar-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 41 publications
0
43
0
4
Order By: Relevance
“…As of today, MET PET has a role in differentiating between tumour recurrence and radiation injury. 13,14 Further, MET PET guides biopsies and delineates tumour margins 15 pre-operatively. MET uptake has been correlated with survival [16][17][18] and malignant tumour progression.…”
mentioning
confidence: 99%
“…As of today, MET PET has a role in differentiating between tumour recurrence and radiation injury. 13,14 Further, MET PET guides biopsies and delineates tumour margins 15 pre-operatively. MET uptake has been correlated with survival [16][17][18] and malignant tumour progression.…”
mentioning
confidence: 99%
“…Nevertheless, a meta-analysis on the diagnostic value of MET PET yielded a pooled sensitivity and specificity of 91 % and 86 % (n = 416) for differential diagnosis of unknown brain lesions while the performance of FDG PET was only moderate with a sensitivity and specificity of 71 % and 77 %, respectively (n = 857) [44]. Concerning FET PET, a meta-analysis of 13 studies including a total of 462 patients yielded a pooled sensitivity of 82% and specificity of 76% for the diagnosis of primary brain tumors [36].…”
Section: Differential Diagnosis Of Brain Tumorsmentioning
confidence: 99%
“…In recent years, the clinical value of [ 11 C]MET has been thoroughly investigated for brain tumors by Glaudemans et al as well as in a meta-analysis by Zhao et al Both studies showed an excellent diagnostic performance of [ 11 C]MET in brain tumor differentiation where the threshold for determination of brain tumors, relying on tumor-tobackground ratio, was determined to be acceptable between 1.5 and 1.9 [112,113]. Furthermore, [ 11 C]MET uptake in the normal brain in comparison to glioma patients offered significant advantages, also for white matter changes, which are normally missed in standard analysis methods [114].…”
Section: Reflections On the Preclinical And Clinical Applications Of mentioning
confidence: 99%